Thermo-analyses of polyaniline and its derivatives - Alves, William F.; Venancio, Everaldo C.; Leite, Fabio L.; Kanda, Darcy H. F. [UNESP]; Malmonge, Luiz F. [UNESP]; Malmonge, Jose A. [UNESP]; Mattoso, Luiz H. C. (Elsevier B.V., 2010)
In this work, is presented the thermal behavior of polyaniline (PAN!) and its derivatives poly(o-ethoxyaniline) (POEA) and poly(o-methoxyaniline) (PUMA), which were studied by using differential scanning calorimetry (DSC), modulated DSC (TMDSC), respectively, and thermal gravimetric analysis (TGA). The results from diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) and thermal analysis showed the formation of crosslinking isomerization reaction during the heating process. The results showed that the maximum weight loss and the crystallinity degree depend on the type of the aromatic ring substituent group, i.e. hydrogen, ethoxy or methoxy. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Polyaniline; DSC; TGA; Poly(o-methoxyaniline); Poly(o-ethoxyaniline)